Characterizations of Cancer Gene Mutations in Chinese Metastatic Breast Cancer Patients - Tao, Zhonghua; Li, Ting; Feng, Zhe; Liu, Chang; Shao, Yilin; Zhu, Mingyu; Gong, Chengcheng; Wang, Biyun; Cao, Jun; Wang, Leipin; Du, Yiqun; Lizaso, Analyn; et al. (Frontiers in Oncology, 2020)
Background: Breast cancer (BC) is a heterogeneous disease. Molecular profiling, which reveals the intrinsic nature among subtypes, has significantly advanced the management of this disease. However, the integration of genomic mutation into this landscape in metastatic breast cancer has not been fully explored. Methods: We performed capture-based targeted sequencing on plasma samples and matched mononuclear cells using an assay to detect 108 BC related genes, spanning 249 kb of human genome, to interrogate the genomic landscape of 290 female Chinese metastatic BC patients. Mutation profiles of mononuclear cells was used as control. Afterwards, we compared the results to the TCGA data set. Results: A total of 2,008 mutations spanning 373 genes were detected from 238 patients, with a positive detection rate of 82.1%. The most frequently mutated gene was TP53(64%), followed by PIK3CA (31%), PTEN (14%) and RB1 (14%). CNAs, including MYC (14.1%), FGFR1 (13.3%), CCND1 (6.6%), FGF3 (6.6%), FGF4 (6.6%) and FGF19 (6.6%) were also detected in our cohort. Less mutation was found in luminal-A as compared to other types (P=0.02). TP53 mutations were significantly more frequent among TNBC and HER2-positive (P<0.01), whereas PIK3CA in luminal-A, luminal-B and HER2-positive (P<0.01). Amplifications in FGF3, FGF4, FGF19, and CCND1 occurred more often in Luminal-A or Luminal-B BC (P<0.001). Pathogenic or likely pathogenic BRCA1/2 germline mutations were detected in 5.9% in the cohort and 4.4% in TNBC subgroup. Maximum allelic fraction (maxAF) of TP53, RB1 and PIK3CA mutations were associated with multiple organ metastasis. Patients with PIK3CA, PTEN and RB1 mutation were more likely to had liver metastasis, whereas ARID1A mutation was significantly associated with bone metastasis. Compared with TCGA BC dataset, Chinese patients had notably more PIK3CA, RB1, PTEN and FGFR1 alterations in TNBC, whereas harbored less MYC, CREBBP, SPTA1, RUNX1T1and PTK2 mutations. No difference in BRCA1/2 mutations were found in metastatic TNBC between our cohort and TCGA dataset. Conclusions: A different gene mutation profiling was elucidated in Chinese metastatic breast cancer patients, justifying further research for evaluation. Liquid biopsy provides a quick, real-time and minimally invasive tool for future clinical trial and routine practice.